Sex differences regarding the effects of arm swing on ground reaction force and trunk movements between track and field athletes - Hiruma, K.; Kariyama, Y. (Scientific Journal of Sport and Performance, 2023)
The purpose of this study was to clarify the sex difference in the effects of arm swing movements of track and field athletes on ground reaction force and trunk movement. Seven male and nine female athletes belonging to a university track and field team were asked to perform arm swings for 10 seconds each under three different conditions (longitudinal, lateral, and original) while in the standing position. Three-dimensional coordinate data for each experimental trial was collected using an automatic optical motion analyser, and ground reaction forces were measured using a force plate. Under the longitudinal condition, the mean acceleration force was greater for males than for females (p < .05), and the operating range of trunk twist angle was significantly greater for females than for males (p < .05). However, under the original condition, there were no significant differences between the sexes in mean acceleration force, but there were significant differences in maximum twist angle and minimum and maximum shoulder abduction angles (p < .05). These results indicate that there are sex differences in trunk movement and ground reaction force depending on the direction of arm swing.